An eco-plastic made of PLA-Kenaf fibre biocomposite for cleaner environment - Anuar, Hazleen; Ahmad, Zuraida; Mat Ali, Adilah; Yusof, Siti Rasyidah; Fuad, Faizah (2010)
Every year more than 100,000,000 polyethylene terephtalate (PET) bottles are used in Malaysia, Singapore and Brunei. Out of this gigantic figure, 85,000,000 PET bottles end up as garbage and caused the landfills to be filled by the PET bottle toxic wastes that leach into the soil. This may pollute and endangers our environment specifically our drinking water. This project focuses on the potential of kenaf fibre (KF) as a reinforcing material for poly(lactic acid) (PLA) biopolymer. PLA is a food grade plastic and kenaf fibre is a kind of natural fibre widely available in Malaysia. The fabrication of kenaf bast fibre reinforced poly(lactic acid) biocomposite is expected to be applied as food and beverages containers with the properties that are comparable to man-made based composite. The kenaf fibre content in the PLA was 5%, 10%, 15% and 20% by weight. PLA-KF biocomposite was extruded using Haake twin screw extruder then injection molded for further mechanical characterisation. The kenaf-fibre aspect ratio is 34. Single fibre tests shown that tensile strength and tensile modulus for KF are 119.6 MPa and 6206.1 MPa, respectively. Processing parameters have been determined by using 10 wt% KF at temperature of 180oC and screw rotation of 150 rpm. The theoretical tensile strength and tensile modulus was also predicted by using parallel rule of mixture and the value then compared with the value obtained via experimental.